Investigation of quality of cost data for life cycle cost analysis in university building maintenance - Bidi, Nor Khalisah; Ayob, Mohd Fairullazi (2015)
Life Cycle Cost (LCC) method has been stated in profession where it can be commonly applied to predict the maintenance and operation cost of the buildings. However, it was observed from the literature study that there is a limitation to access on the cost data input for LCC of building maintenance practice. This paper presents a study on the investigation of quality of data for LCC as input in university building maintenance practice.The study being reported in this paper is derived from 6 months programme of research carried by the first author to determine the readiness of the implementation of Life Cycle Costing approach in the university building maintenance practice in IIUM. The methodology designed for the study is a qualitative research strategy that comprises of two approaches, which are literature review and semi-structured interview. The key findingS of the study have been established that IIUM is not ready to implement life cycle costing practice in university building maintenance due to the problem of getting quality, current and reliable data as input for producing reliable LCC output.